Effect of fluoride dentifrice and casein phosphopeptide-amorphous calcium phosphate cream with and without fluoride in preventing enamel demineralization in a pH cyclic study - Priscila de Pinto Sinfiteli; Thereza Christina Lopes Coutinho; Patrícia Regina Almeida de Oliveira; Wesley Felisberto Vasques; Leandra Matos Azevedo; André Maues Brabo Pereira; Monica Almeida Tostes
Abstract Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) complexes are anticariogenic and capable of remineralizing the early stages of enamel lesions. The use of fluoride prevents dental decay and the association of CPP-ACP with fluoride can increase remineralization. Objective: To evaluate the effect of CPP-ACP and CPP-ACPF creams associated with a fluoride dentifrice to prevent enamel demineralization in a pH cyclic model. Material and Methods: Previously selected by surface microhardness (SH) analysis, human enamel blocks (n = 56) were submitted to daily treatment with dentifrice in a pH-cycling model. The enamel blocks were divided into four groups; G1: Crest™ Cavity Protection - Procter & Gamble (1,100 ppmF of NaF); G2: Crest™ +MI Paste (MP) - Recaldent™ GC Corporation Tokyo, Japan); G3: Crest™ + MI Paste Plus (MPP) - Recaldent™ 900 ppm as NaF, GC Corporation Tokyo, Japan), and G4: control, saliva. Specimens were soaked alternatively in a demineralizing solution and in artificial saliva for 5 d. The fluoride dentifrice, with proportion of 1:3 (w/w), was applied three times for 60 s after the remineralization period. The undiluted MP and MPP creams were applied for 3 m/d. After cycling, SH was re-measured and cross section microhardness measurements were taken. Results: The SH values observed for the groups G3 (257±70), G1 (205±70), and G2 (208±84) differed from the G4 group (98±110) (one-way ANOVA and Tukey's post hoc test). There were no differences between the groups G1xG2, G2xG3, and G1xG3 for demineralization inhibition. The percentage of volume mineral showed that, when applied with fluoride dentifrice, MPP was the most effective in preventing enamel demineralization at 50 µ from the outer enamel surface (Kruskal-Wallis and Mann Whitney p<0.05). Conclusion: Fluoride dentifrice associated with CPP-ACPF inhibited subsurface enamel demineralization.